Diastolic tolerance to systolic pressures closely reflects systolic performance in patients with coronary heart disease - Leite-Moreira, AF (2012)
In animal experiments, elevating systolic pressures induces diastolic dysfunction and may contribute to congestion, a finding not yet translated to humans. Coronary surgery patients (63 +/- 8 years) were studied with left ventricular (LV) pressure (n = 17) or pressure volume (n = 3) catheters, immediately before cardiopulmonary bypass. Single-beat graded pressure elevations were induced by clamping the ascending aorta. Protocol was repeated after volume loading (n = 7). Consecutive patients with a wide range of systolic function were included. Peak isovolumetric LV pressure (LVPiso) ranged from 113 to 261 mmHg. With preserved systolic function, LVP elevations neither delayed relaxation nor increased filling pressures. With decreasing systolic function, diastolic tolerance to afterload progressively disappeared: relaxation slowed and filling pressures increased (diastolic dysfunction). In severely depressed systolic function, filling pressures increased even with minor LVP elevations, suggesting baseline load-dependent elevation of diastolic pressures. The magnitude of filling pressure elevation induced in isovolumetric heartbeats was closely and inversely related to systolic performance, evaluated by LVPiso (r = -0.96), and directly related to changes in the time constant of relaxation tau (r = 0.95). The maximum tolerated systolic LVP (without diastolic dysfunction) was similarly correlated with LVPiso (r = 0.99). Volume loading itself accelerated relaxation, but augmented afterload-induced upward shift of filling pressures (7.9 +/- 3.7 vs. 3.0 +/- 1.5; P < 0.01). The normal human response to even markedly increased systolic pressures is no slowing of relaxation and preservation of normal filling pressures. When cardiac function deteriorates, the LV becomes less tolerant, responding with slowed relaxation and increased filling pressures. This increase is exacerbated by volume loading.